Essays in applied microeconomics. Research collaboration and dissemination in economics - KULD, LUKAS VALENTIN (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2018)
This dissertation studies the production and dissemination of economic research in three essays. The chapters explore data on economic research articles and their authors to study, first, the effect of national borders on the international dissemination of economic research along cultural and technological links, second, the rise of collaborations between economists, and, third, the benefit of local research clusters. Chapter 1 provides an introduction and outlines the specific research questions that are explored in this dissertation. Chapter 2 examines the existence of a border effect in the dissemination of knowledge in economics using a gravity model framework and novel data on domestic and international citation flows in economic research between 1970 and 2016. The citation data are linked to geographic and cultural distance measures, as well as novel indicators for virtual proximity and English proficiency. The results show that (i) citation patterns follow the law of gravity; (ii) citations in economics exhibit a strong and significant home bias by an overall factor of 1.9 for all ten leading countries (a 90 percent higher propensity to cite domestic articles); (iii) bilaterally low levels of English proficiency are associated with a cost of up to 30 percent, while similarity in English proficiency is insignificant for the total sample; (iv) countries with closer early internet ties have significantly higher shares of bilateral citations of up to .25 percent for a 1 percent increase in internet hyperlinks. Over time, the estimated impact of home bias as well as geographic and cultural distance declines but remains significant. Chapter 3 presents new evidence on several features of co-authorship in articles in economic journals. It builds on previous work by reviewing the key literature relating to the rise in co-authorship in economics. The empirical analysis draws on around 175,000 articles in the top 255 journals, over the period 1996 to 2014. The rises in quarto-plus and cross-country co-authored papers are striking, as are the differences in citations per article and citations per author. There is evidence of an alphabetical ordering of authors as the standard in co-authored papers in top journals with no downward trend evident over time. A correlation between co-authorship and career stage is observed with young authors publishing significantly more solo-authored articles. Chapter 4 studies benefits from local research linkages. Recent research observes a declining or no return from the quality of local colleagues on a researcher's productivity but positive spill-overs between co-authors. The findings of this chapter show benefits from research linkages between department colleagues below the level of co-authorship. Using data from the CVs of around 1,000 highly-cited economists, this chapter tests whether take-up of a research article by future research is increased if it links with the research of local colleagues. The estimates show that ``high-profile'' research that references articles by local colleagues receives significantly more citations than comparable work by the same authors. There is no dissemination benefit for less prominently published ``routine-type'' research or for colleagues without a thematic link. Chapter 5 concludes the dissertation.
APPROVED
Keywords: academic research; research collaboration; productivity; research dissemination